Diversity statistics of onomastic data reveal social patterns in Hebrew Kingdoms of the Iron Age - Ariel Vishne; Mitka R. Golub; Eli Piasetzky; Israel Finkelstein; Barak Sober (Proceedings of the National Academy of Sciences, 2025)
The distribution of personal names provides unique, yet often overlooked, insight into modern and historical societies. This study employs diversity statistics—commonly used in ecology—to analyze onomastic data from Iron Age II archaeological excavations in the Southern Levant (950–586 BCE). Our findings reveal higher onomastic diversity in the Kingdom of Israel compared to Judah, suggesting a more cosmopolitan society. We also observe a decrease in name diversity in Judah over time, potentially reflecting sociopolitical changes. Center/periphery analysis shows contrasting patterns in Israel and Judah. These results provide insights into social dynamics, cultural interactions, and identity formation in these ancient societies. Our methodology, validated using supplementary archaeological data, as well as modern datasets, offers a robust framework for applying diversity statistics across various modern and historical contexts.